The Effect of Welded Splice with Predetermined Gap of Concrete Spun Pile on The Response of Low Strain Integrity Test - Gogot Setyo Budi; Levin S. Tanaya (Civil Engineering Dimension, 2022)
This paper presents the velocity wave of concrete spun piles with welded splice. The stress wave velocity was recorded using Pile Integrity Test. Two specimens were prepared in the experiment. The first sample was prepared visually no gap between the two end-plates of connected  piles, while the second  specimen was prepared by inserting 5mm thick steel plate into the splice to create a gap in its connection. The results show that a spike of reflecting stress wave still develops at the splice with and without gap, regardless the splice was welded in full circle. The relatively high spikes of reflecting waves at pile toe are noticed for both specimens with and without gaps. It shows that the full welded splice able to transfer stress wave velocity.  A good quality of welded splice can be indicated by the reflecting wave at the pile toe, regardless the reflecting wave development at the splice.